Clinical and radiographic evaluation of surgical treatment of zygomatic fractures using 1.5 mm miniplates system - Hasse, Paulo Norberto [UNESP]; Gealh, Walter Cristiano [UNESP]; Pereira, Cassiano Costa Silva [UNESP]; Coradazzi, Luiz Francisco [UNESP]; Magro Filho, Osvaldo [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP] (Scientific Research Publishing, 2011)
Fractures of the zygomaticomaxillary complex are among the most common face traumas. Based upon the complexity and great variety of reported diagnoses and treatments, the proposal of this study was to evaluate, clinically and radiographically, unilateral zygomatic fractures treated through internal rigid fixation with miniplates and screws of 1.5 mm. Material and Method: 15 patients with unilateral fractures of the zygomaticomaxillary complex were analyzed, and compared with 15 patients without fractures so that a comparative analysis of the area and the perimeter of the orbital cavities could be made, as well as the distance from the nasal point to the zygomatic prominence between both groups. Results: In the radiographic analysis, the both groups presented similarity in the perimeter and in the area of the orbital cavities. Concerning the distance from the nasal point to the zygomatic prominence, only the operated group showed a significant difference between the sides, even though clinically the observation of the asymmetry had been absent or discreet. Conclusions: The treatment of unilateral fractures of the zygomaticomaxillary complex with the use of plates and screws of the 1.5 mm system proved to be effective, showing good esthetic results and low complication rates.